Analisis Rasio Energi Daur Ulang Panas pada Produksi Biodiesel Secara Non-Katalitik - Armansyah Halomoan Tambunan; . Furqon; . Joelianingsih; Tetsuya Araki; Hiroshi Nabetani (Jurnal Ilmu Pertanian Indonesia, 2012)
Energy consumption in non-catalytic biodiesel production is still high, and needs to be reduced to the optimum level. It can be accomplished by recirculating the heat being used in the process by using heat exchanger. The objective of this study is to analyze the energy ratio of the system as influenced by the heat recirculation through a heat exchanger. This experiment used a superheated methanol vapor method for non-catalytic biodiesel production. The study was started with the determination and calculation of physical and thermal properties of materials to be used (palm olein, methanol, and methyl ester), continued with the designing of the heat exchanger, the experiment itself, and the energy ratio analysis. The process was occured in semi-batch mode with 3 levels of methanol flow rate, i.e., 1.5, 3.0, and 4.5 mL/minute, at reaction temperature of 290 °C. The results show that heat recirculation by using heat exchanger can increase the energy ratio from 0.84 to 1.03, according to the definition that energy ratio is the ratio between energy content of the biodiesel to the total energi of the feedstock and the process energy. If the energy ratio is defined as the ratio between the increase in energy content of the biodiesel from its feedstock to the process energy, the energy ratio was found to be 7.85, 2.98, and 2.87 for the respective methanol flow rate of 1.5, 3.0, and 4.5 mL/min.